Enhancing egg cartons' sound absorption coefficient with recycled materials. Issue 2 (June 2017) - Satwiko, Prasasto; Gharata, Verza Dillano; Setyabudi, Herybert; Suhedi, Fefen
Egg cartons have popularly been used as sound absorbers because they are inexpensive, easy to install and easily available. However, acoustic experts have demonstrated that egg cartons are bad sound absorbers. This study developed Enhanced Egg Carton – Dry and Enhanced Egg Carton – Wet using additional recycled materials (shredded rice straw paper, textile waste, 2-cm cut rice straws) to improve the cartons' sound absorption coefficient while retaining their original advantages. Enhanced Egg Carton – Dry and Enhanced Egg Carton – Wet were tested based on the ASTM C423-02 method of sound absorption measurement. Enhanced Egg Carton – Dry has a noise reduction coefficient of 0.6 and a sound absorption average of 0.59, while Enhanced Egg Carton – Wet has a noise reduction coefficient of 0.54 and sound absorption average of 0.54. The maximum sound absorption coefficients of Enhanced Egg Carton – Dry and Enhanced Egg Carton – Wet are, respectively, 0.77 at 500 Hz and 0.67 at 630 Hz. Enhanced Egg Carton – Dry has a sound absorption coefficient ⩾0.5, between 315 and 2500 Hz, which makes it able to absorb sound energy of the lower to upper mid-range frequencies. With their high sound absorptivity at mid-range frequencies, Enhanced Egg Carton – Dry and Enhanced Egg Carton – Wet are suitable for mosques and auditoriums, where the human voice is the dominant noise source and where an inexpensive sound absorber is needed. The production of Enhanced Egg Carton – Dry and Enhanced Egg Carton – Wet is so simple that users can do it themselves using basic home tools.